Navigating PRKCSH’s impact on cancer: from N-linked glycosylation to death pathway and anti-tumor immunity - Cressey, Ratchada; Han, Moe Thi Thi; Khaodee, Worapong; Xiyuan, Guo; Qing, Yuan (Frontiers in Oncology, 2024)
PRKCSH, also known as Glucosidase II beta subunit (GluIIβ), is a crucial component of the endoplasmic reticulum (ER) quality control system for N-linked glycosylation, essential for identifying and eliminating misfolded proteins. Glucosidase II consists of the catalytic alpha subunit (GluIIα) and the regulatory beta subunit (GluIIβ), ensuring proper protein folding and release from the ER. The induction of PRKCSH in cancer and its interaction with various cellular components suggest broader roles beyond its previously known functions. Mutations in the PRKCSH gene are linked to autosomal dominant polycystic liver disease (ADPLD). Alternative splicing generates distinct PRKCSH isoforms, which can influence processes like epithelial-mesenchymal transition (EMT) and the proliferation of lung cancer cells. PRKCSH's involvement in cancer is multifaceted, impacting cell growth, metastasis, and response to growth factors. Additionally, PRKCSH orchestrates cell death programs, affecting both autophagy and apoptosis. Its role in facilitating N-linked glycoprotein release from the ER is hypothesized to assist cancer cells in managing increased demand and ER stress. Moreover, PRKCSH modulates anti-tumor immunity, with its suppression augmenting NK cell and T cell activity, promising enhanced cancer therapy. PRKCSH's diverse functions, including regulation of IGF1R and IRE1α, implicate it as a therapeutic target and biomarker in cancer immunotherapy. However, targeting its glucosidase II activity alone may not fully counteract its effects, suggesting broader mechanisms in cancer development. Further investigations are needed to elucidate PRKCSH's precise role and validate its therapeutic potential in cancer treatment.